Evolusi Pemikiran Ekonomi Islam Monzer Kahf: SLR 2020-2024 - Asieh, Ikeu Triana Yulie; Chairunnisa, Chairunnisa; Wartoyo, Wartoyo (International Journal Labs, 2025)
This study examines the contributions and evolution of Monzer Kahf’s Islamic economic thought through a Systematic Literature Review of scientific publications from 2020 to 2024. The background of this research is driven by the growing academic interest in Kahf’s ideas as a response to various contemporary economic challenges, such as excessive consumption and unequal wealth distribution. The research method involved reviewing 15 scholarly articles that met inclusion criteria and analyzing them thematically to capture the development of Kahf’s thought. The findings indicate that Kahf’s ideas have significantly evolved and serve as a key reference in important topics such as Islamic consumption, the concept of homo Islamicus, final spending, and Sharia fiscal policy. These concepts reflect an Islamic economic approach that integrates rationality, spirituality, and social justice. The study highlights Monzer Kahf’s strategic role in shaping an Islamic economic framework that is not only theoretical but also practical and contextually relevant to contemporary economic issues. This research strengthens the understanding that Kahf’s thought forms a crucial foundation for the development of modern Islamic economics capable of addressing current social and economic dynamics. Thus, this study makes a significant academic contribution to the theory and practice of Islamic economics.